ҚАЗАҚСТАН РЕСПУБЛИКАСЫНДАҒЫ ƏКІМШІЛІК-ЮРИСДИКЦИЯЛЫҚ ҚЫЗМЕТ: ƏКІМШІЛІК ЮРИСДИКЦИЯ ТҮСІНІГІ МЕН НЕГІЗГІ ПРИНЦИПТЕРІ (Journal of actual problems of jurisprudence, 2019)
To given clause the author on separate examples of researches A. Taranova., M. Vaiberga., M. Kozlova. and other sources analyzes the basicquestions of an administrative - legal service in Republic of Kazakhstan, concept and basic principles of administrative law: the purposes ofadministrative - legal services, realization of the administrative claims, kinds of the used sanctions used measures, task of the authorized bodies,objective position of the validity.